Efektivitas Media Sosial Instagram Sebagai Sarana Komunikasi Publik Pada Dinas Lingkungan Hidup dan Kebersihan Kota Pekanbaru - Susi Artuti Erda Dewi; Rosmala; Debby Kurniadi (JURNAL SOSIO-KOMUNIKA, 2023)
The author focuses on the foresight of the Pekanbaru City Environment and Sanitation Service in utilizing Instagram social media as a means to actively communicate with other Instagram social media users, especially the people of Pekanbaru City. The purpose of this study is to describe the use of social media Instagram as a means of public communication at the Pekanbaru City Environment and Sanitation Service. This research uses the library research method where the object is searched with various library information such as books, scientific journals, magazines, newspapers and documents. The results of data analysis include data reduction, data presentation and conclusion. The findings obtained by the author in this study are based on the Shimp theory that the use of Instagram social media as a means of public communication at the Pekanbaru City Environment and Sanitation Service has been effective. complaints of garbage in the environment of the Pekanbaru city community so it is only natural that the Pekanbaru City Environment and Sanitation Service led by Hendra Afriadi, SH., M.Si succeeded in getting the ADIPURA 2022 certificate award, then the Pekanbaru City Environment and Sanitation Service is considered consistent in providing posts full of positive information and adding new knowledge to the public. society, although sometimes it is found that there are several posts that look monotonous even though the contents of the message from each of these posts are different.